Carbon dioxide capture from flue gases using microalgae: Engineering aspects and biorefinery concept - J. C. M. Pires (2012)
Carbon dioxide (CO2) is one of the most important contributors for the increase of the greenhouse effect. CO2 concentrations are increasing in the last decades mainly due to the increase of anthropogenic emissions. To reduce the effects caused by this environmental problem, several technologies were studied to capture CO2 from large emission source points: (i) absorption; (ii) adsorption; (iii) gas-separation membranes; and (iv) cryogenic distillation. The resulting streams with high CO2 concentrations are transported and stored in geological formations. However, these methodologies, known as carbon capture and storage (CCS) technologies, are considered as short-term solutions, as there are still concerns about the environmental sustainability of these processes. A promising technology is the biological capture of CO2 using microalgae. These microorganisms can fix CO2 using solar energy with efficiency ten times greater than terrestrial plants. Moreover, the capture process using microalgae has the following advantages: (i) being an environmental sustainable method; (ii) using directly the solar energy; and (iii) co-producing high added value materials based on biomass, such as human food, animal feed mainly for aquaculture, cosmetics, medical drugs, fertilizers, biomolecules for specific applications and biofuels. Approaches for making CO2 fixation by microalgae economically competitive in comparison with CCS methodologies are discussed, which includes the type of bioreactors, the key process parameters, the gaseous effluents and wastewater treatment, the harvesting methods and the products extracted by microalgal biomass.